International Perspectives on Educating for Democracy in Early Childhood Recognizing Young Children as Citizens (Taylor & Francis, 2023)
This book brings together established and emerging scholars from around the globe to highlight new directions for research on young children as active, engaged citizens of classrooms. Divided into three sections, the volume draws on innovative methods to explore diverse conceptualizations of citizenship, children's understandings, and effective practice. Rejecting traditional views of children as citizens-in-preparation, the volume explores how young children can and do live as citizens, and how early childhood educational settings serve as civic forums. Chapters discuss the child-as-citizen in relation to issues including gender, class, race, tribal status, and linguistic diversity, and ultimately illustrate how sociocultural processes in early years settings can be harnessed to promote the development of democratic dispositions and skills. This book establishes citizenship enactment in early childhood education as a robust and growing research area with the potential to shape research, policy, and practice worldwide. As such, it will appeal to researchers and academics with an interest in citizenship education, democracy, and early childhood education, as well as postgraduate students of teacher education and those working across international and comparative education more broadly.
English
Keywords: Education; as, Childhood, Children, Citizens, Democracy, DeZutter, Early, Educating, for, in, International, Lee, on, Perspectives, Recognizing, Stacy, Young